Hydrogen Embrittlement and Cohesive Behavior of an Ultrahigh-Strength Lath Martensitic Steel of Tendon Bars for Structural Engineering - Patricia Santos; Andrés Valiente; Mihaela Iordachescu (Applied Sciences)
This paper assesses experimentally and theoretically the hydrogen-assisted cracking sensitivity of an ultrahigh-strength lath martensitic steel, recently used to manufacture tendon rods for structural engineering. The experimental values of the J-integral were obtained by tensile testing up to failure precracked SENT specimens in air, as an inert environment and in a thiocyanate aqueous solution, as a hydrogen-promoter medium. In parallel, the theoretical resources necessary to apply the Dugdale cohesive model to the SENT specimen were developed from the Green function in order to predict the J-integral dependency on the applied load and the crack size, with the cohesive resistance being the only material constant concerning fracture. The comparison of theoretical and experimental results strongly supports the premise that the cohesive crack accurately models the effect of the mechanisms by which the examined steel opposes crack propagation, both when in hydrogen-free and -embrittled conditions. The identification of experimental and theoretical limit values respectively involving a post-small-scale-yielding regime and unstable extension of the cohesive zone allowed for the value of the cohesive resistance to be determined, its condition as a material constant in hydrogen-free medium confirmed, and its strong decrease with hydrogen exposure revealed.